2017
DOI: 10.1039/c6ra27850g
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective Eu(iii) spectroscopy of highly efficient luminescent mixed-metal Pb(ii)/Eu(iii) coordination polymers

Abstract: Novel coordination polymers based on Pb1−xEux–BDC (x = 0.05–0.50, BDC = 1,4-benzenedicarboxylic acid) are reported with a maximum emission quantum yield of 69 ± 7%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
(80 reference statements)
1
6
0
Order By: Relevance
“…It can be observed that the ligand salt shows signals centered in 1544 and 1389 cm À1 referring to the n as COO À and n s COO À stretches, which are shifted in relation to the EuBDC spectrum, indicating the coordination of the compound. 40 The spectrum of the CDots/EuBDC (Fig. 4; red line) shows signals very similar to those observed for the EuBDC (Fig.…”
Section: Porosity Chemical and Thermal Analysissupporting
confidence: 67%
See 1 more Smart Citation
“…It can be observed that the ligand salt shows signals centered in 1544 and 1389 cm À1 referring to the n as COO À and n s COO À stretches, which are shifted in relation to the EuBDC spectrum, indicating the coordination of the compound. 40 The spectrum of the CDots/EuBDC (Fig. 4; red line) shows signals very similar to those observed for the EuBDC (Fig.…”
Section: Porosity Chemical and Thermal Analysissupporting
confidence: 67%
“…The EuBDC MOF was prepared following a methodology reported elsewhere. 40 0.5 mmol of Eu(NO 3 ) 3 ·6H 2 O, 0.5 mmol of disodium terephthalate (Na 2 BDC), 5 mmol of polyvinylpyrrolidone, and 65 mL of distilled water were mixed (in a Becker), and the entire system immersed in an ultrasonic bath for 5 min at room temperature. Afterwards, the product was centrifuged, separated, and washed three times with ethanol using successive centrifugation for 10 min at 8000 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the relative intensity of the 5 D 0 → 7 F 2 (617 nm) transition depends on the coordination environment and symmetry around the Eu 3+ centers . This indicates that in Ln-MOF 2 Eu 3+ ions have low symmetry and the inversion center is absent in accordance with the Judd–Ofelt theory . In Ln-MOF 2 , 5 D 0 → 7 F 0 (548 nm) and 5 D 0 → 7 F 4 (697 nm) are the shortest- and longest-wavelength transitions, are electric as well as magnetic-dipole forbidden transitions, and possibly arise because of the crystal-field-induced J -mixing effect …”
Section: Resultsmentioning
confidence: 75%
“…92 This indicates that in Ln-MOF 2 Eu 3+ ions have low symmetry and the inversion center is absent in accordance with the Judd−Ofelt theory. 93 In Ln-MOF 2, 5 D 0 → 7 F 0 (548 nm) and 5 D 0 → 7 F 4 (697 nm) are the shortest-and longest-wavelength transitions, are electric as well as magnetic-dipole forbidden transitions, and possibly arise because of the crystal-field-induced J-mixing effect. 94 Ln-MOF 4 exhibits typical solid-state photoluminescent emission of a ligand-sensitized Tb III ion upon excitation at 361 nm.…”
Section: S6mentioning
confidence: 99%
“…Toxic metal ions and organic pollutants released in environmental water could cause tremendous adverse effects on the environment and human health; , for example, intake of Fe 3+ , Cu 2+ , Ag + , Cd 2+ , and anilines might cause Parkinson’s, pancreas, liver, heart, and Alzheimer’s diseases, , organ failure, cell toxicity, and certain cancers. , However, most of the current detection and capture methods (i.e., micro-solid phase extraction, atomic absorption spectrometry, chemiluminescence techniques, inductively coupled plasma mass spectrometry (ICP-MS), fiber-optical chemosensing method, electrochemical method, , high-performance liquid chromatography (HPLC), and gas chromatography (GC)) require complicated sample pretreatment processes, sophisticated instrumentation, high cost, and long analytical processing time in a credited laboratory. In recent years, luminescent lanthanide-metal–organic frameworks (Ln-MOFs), which showcase a ratiometric “turn-up” or “turn-down” fluorescence response depending on the energy transfer efficiency through host–guest interactions, have received much attention and demonstrated important advantages, such as improved rapidity, operability, and sensitivity. …”
Section: Introductionmentioning
confidence: 99%